Reference genome for a novel family of RNA viruses from subarctic ponds, 2011 - Derek Taylor (Arctic Data Center, 2017)
Very little is known of viral diversity in polar freshwater ponds and about the effects that climate-induced habitat changes in these regions will have on virus-host interactions. Our results show that at the tundra-boreal boundary, a hidden viral landscape is being altered, as infected boreal phantom midges colonize tundra ponds. The family of RNA viruses involved is novel (Phasmaviridae) and its discovery suggests that ancient and highly divergent viruses remain undetected in nature and may offer fresh insight into host reservoirs, potential sources of emerging disease and major lifestyle shifts in the evolutionary history of viruses. The data here include the reference genome and annotation of Kigluaik phantom orthophasmavirus (the type species) isolated from phantom midges in a subarctic pond near Salmon Lake Alaska.